2005
DOI: 10.1136/jech.2004.021584
|View full text |Cite
|
Sign up to set email alerts
|

Can we evaluate population screening strategies in UK general practice? A pilot randomised controlled trial comparing postal and opportunistic screening for genital chlamydial infection

Abstract: Study objective: To assess whether opportunistic and postal screening strategies for Chlamydia trachomatis can be compared with usual care in a randomised trial in general practice. Design: Feasibility study for a randomised controlled trial. Setting: Three West of Scotland general medical practices: one rural, one urban/deprived, and one urban/affluent. Participants: 600 women aged 16-30 years, 200 from each of three participating practices selected at random from a sample of West of Scotland practices that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
0
27
0
2
Order By: Relevance
“…This necessitates an extremely large sample size and, accordingly, considerable resources. It would also be extremely difficult to gain ethical approval for a cohort study designed to monitor adverse outcomes among women with untreated chlamydial infection within a policy context that actively promotes testing and treatment 22. There is already good evidence that treating people with genital chlamydial infection is beneficial in relation to short-term morbidity;2 5 moreover, numerous case–control studies have demonstrated that women with infertility have a significantly greater chance of having been infected with chlamydia than those who are fertile 5 6.…”
Section: Discussionmentioning
confidence: 99%
“…This necessitates an extremely large sample size and, accordingly, considerable resources. It would also be extremely difficult to gain ethical approval for a cohort study designed to monitor adverse outcomes among women with untreated chlamydial infection within a policy context that actively promotes testing and treatment 22. There is already good evidence that treating people with genital chlamydial infection is beneficial in relation to short-term morbidity;2 5 moreover, numerous case–control studies have demonstrated that women with infertility have a significantly greater chance of having been infected with chlamydia than those who are fertile 5 6.…”
Section: Discussionmentioning
confidence: 99%
“…A concern was to optimise use of the software during consultations so, in addition to standard intervention and control arms, an exploratory trial included an "adaptive arm," which permitted the software and protocols to be varied during the trial in response to comments from practitioners and reasons identified for low use 20 Table 3 | Optimising the evaluation: example of community based screening for genital Chlamydia trachomatis infection 24 …”
Section: Collecting Datamentioning
confidence: 99%
“…[172][173][174] Furthermore, three papers identified in this review reported the involvement of receptionists in distributing leaflets or discussing screening with patients. [175][176][177] Treatment of chlamydia infection and partner notification can be provided by programme area screening team offices.…”
Section: Chlamydia Screeningmentioning
confidence: 99%